The Commodification of Religious Values in Indonesian Hijab Shampoo Advertisements - Hariyanti, Rosana; Hapsari, Dyah Eko (Universitas Negeri Surabaya, 2024)
Beauty has become a precious commodity that the cosmetics business has captured by presenting the best image possible, particularly through advertising. The huge increase in the number of hijab wearers (hijabers) in Indonesia over the last few decades is one phenomenon to which the business has responded. This raises the topic of how religion is depicted in commercials for hijab shampoo products. These commercials are deconstructed to locate meaning, which leads to commodification practices using a semiotic approach, particularly Roland Barthes' examination of myth. The examination is then carried out from a sociological standpoint, using Karl Marx's idea of commodification. This qualitative research method uses content analysis on ten different hijab shampoo advertising from three different international manufacturers. The findings suggest that the advertisements are more than merely conveying the word that the product is useful for hair maintenance. There are also messages to wear the hijab regularly, that the hijab does not limit women's activities, and that hair health has ramifications for psychological disorders. The image depicted is a type of commodification in which the hijab is paired with cosmopolitanism, and the sacred significance of the headscarf itself is diminished.